(3TQM deYI GdETQGb aj GdGTJbGbs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg gPG JhVjM deYI GdETQGb aj CeKdI GdGTJbGb fXeJbj GdOjf GdSHcj SejJg TQM deYI GdETQGb aj GdGTJbGbs
(3BNQgG (B:s
(3GdTjN TgGH GdOjf GdYHGOj aj QHjY GdChd GdTjN YVO GdOjf GdSjQGaj djdI GdSHJ SGOS YTQ QHjY GdBNQ hehdOg SfI KdGK YTQIs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B886(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 1564s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs